Atypical proliferating mucinous tumors of gigantic dimensions - Likić-Lađević Ivana (Vojnosanitetski Pregled, 2008)
Background. Ovarian tumors of low malignant potential (LMP) are also known as atypically proliferating tumors. Ovarian tumors of LPM account for approximately 15% of all epithelial ovarian cancers. Mean age of occurrence is 40 years and they are 15-20 cm in diameter. Case report. A 32-year-old female patient was hospitalized as an urgent case with a large tumor mass that filled the entire abdomen. Cyst was 100 × 70 cm dimensions belonging to the right ovary and filled with 18 liters of content. Right adnexectomy, resection of the second ovary, as well as biopsy of the omentum were performed. Lymphadenectomy of the right iliac and obturator area was also performed. After receiving definitive histopathological results it was decided to perform a radical reoperation. On the 10th postoperative day relaparotomy, total hysterectomy and left adnexectomy were performed. The patient was released on the 6th postoperative day. She used to come to regular examinations up to date. Conclusion. This case is a proof that LMP tumors have low malignant potential, they grow slowly and can reach great proportions.